A hybrid simulation approach for microtunneling construction planning. Issue 3 (10th February 2021) - Moharrami, Saeid; Taghaddos, Maedeh; RazaviAlavi, SeyedReza; AbouRizk, Simaan
Abstract : Purpose: Construction planning for microtunneling projects is a complex process due to the high level of uncertainties inherent in underground construction and the interdependent nature of decision variables. Simulation is a suitable decision-making tool to account for uncertainties and to model complex dependencies among decision variables. This paper aims to improve microtunneling construction planning by using simulation. Design/methodology/approach: This study proposes a hybrid simulation approach that combines discrete event simulation (DES) with continuous simulation (CS) for microtunneling construction planning. In this approach, DES is used to model construction processes at the activity level and CS is used to model the continuous flow of soil material in the system. Findings: To demonstrate the capability of the proposed approach in construction planning of microtunneling projects, different construction plan scenarios are compared in a microtunneling case study. The results of the case study show suitability of the hybrid DES-CS approach in simulating microtunneling construction processes and the practicality of the approach for identifying the most efficient construction plan. Originality/value: This study proposes a new modeling approach for microtunneling construction processes using hybrid simulation and provides decision support at the construction planning stage of projects.